Relationship between mean platelet volume-to-lymphocyte ratio and coronary artery abnormalities in Kawasaki disease. (16th April 2018) - Bozlu, Gulcin; Karpuz, Derya; Hallioglu, Olgu; Unal, Selma; Kuyucu, Necdet
Abstract: Objectives: Recently, mean platelet volume-to-lymphocyte ratio has emerged as a novel parameter of inflammation. No study has investigated the role of mean platelet volume-to-lymphocyte ratio in children with Kawasaki disease. We aimed to evaluate the relationship between mean platelet volume-to-lymphocyte ratio and coronary artery abnormalities in Kawasaki disease. Methods: Between January 2008 and January 2017, a total of 58 children with Kawasaki disease and 42 healthy subjects matched for sex and age were enrolled. Before the treatment, transthoracic echocardiography for all children was performed. Clinical and laboratory results including mean platelet volume, platelet distribution width, red blood cell distribution width, and counts of platelets, neutrophils, lymphocytes, and white blood cells, erythrocyte sedimentation rate, and C-reactive protein levels were measured. Mean platelet volume-to-lymphocyte ratio was calculated as mean platelet volume divided by lymphocyte count. Results: Compared with healthy controls, mean platelet volume-to-lymphocyte ratio was significantly lower in the children with Kawasaki disease (p<0.01). A total of 14 patients (24.1%) had incomplete Kawasaki disease and 15 (25.8%) children with Kawasaki disease had coronary involvement. Mean platelet volume-to-lymphocyte ratio was significantly lower in patients with coronary artery abnormalities (p<0.01). According to receiver operating characteristic curve analysis performed for the prediction of coronary artery abnormalities, the best cut-off point for mean platelet volume-to-lymphocyte ratio was 2.5 (area under curve=0.593, sensitivity 53.3%, specificity 51.1%). Conclusion: It was first shown that the children with Kawasaki disease have lower mean platelet volume-to-lymphocyte ratio compared with control subjects. Mean platelet volume-to-lymphocyte ratio may be helpful in predicting coronary artery lesions in patients with Kawasaki disease.